Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s12325-021-02006-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Chronic Kidney Disease: A Systematic Literature Review of Randomized Controlled Trials

Abstract: Delaying disease progression and reducing the risk of mortality are key goals in the treatment of chronic kidney disease (CKD). New drug classes to augment renin-angiotensin-aldosterone system (RAAS) inhibitors as the standard of care have scarcely met their primary endpoints until recently. This systematic literature review explored treatments evaluated in patients with CKD since 1990 to understand what contemporary data add to the treatment landscape. Eighty-nine clinical trials were identified that had enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…Therapeutic options to decelerate kidney function decline are limited. In addition to pharmacological inhibitors of the RAAS-system 9 , the recent introduction SGLT2 inhibitors show promising reno-protective effects 10 , 11 . An understanding of the mechanisms of kidney function decline and the developing of new therapeutic options is thus of high clinical and public health relevance 7 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic options to decelerate kidney function decline are limited. In addition to pharmacological inhibitors of the RAAS-system 9 , the recent introduction SGLT2 inhibitors show promising reno-protective effects 10 , 11 . An understanding of the mechanisms of kidney function decline and the developing of new therapeutic options is thus of high clinical and public health relevance 7 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Data from recent clinical studies have suggested potential benefits of SGLT2i on kidney outcomes in individuals with CKD, 11,12 and current ADA guidelines recommend the use of SGLT2i in those with eGFR ≥25 mL/min/1.73 m 2 or UACR ≥300 mg/g 15 . Our data did not reveal any notable trends in SGLT2i prescriptions according to UACR level, but this may reflect the infrequent prescription of SGLT2i in the analysis period and the timeframe of our dataset, most of which was prior to the completion of clinical trials evaluating SGLT2i in CKD and the recommendation for these agents as part of first‐line therapy regimens in individuals with CKD and T2D 15 .…”
Section: Discussionmentioning
confidence: 62%
“…26 Insulin use is also associated with significant burden in terms of administration, side effects and cost, and does not confer the documented benefits seen across various cardiovascular and kidney outcomes with some oral medications, such as SGLT2i, finerenone and GLP-1 receptor antagonists. 15,[27][28][29][30] Data from recent clinical studies have suggested potential benefits of SGLT2i on kidney outcomes in individuals with CKD, 11,12 and current ADA guidelines recommend the use of SGLT2i in those with eGFR ≥25 mL/min/1.73 m 2 or UACR ≥300 mg/g. 15 Our data did not reveal any notable trends in SGLT2i prescriptions according to UACR level, but this may reflect the infrequent prescription of SGLT2i in the analysis period and the timeframe of our dataset, most of which was prior to the completion of clinical trials evaluating SGLT2i in CKD and the recommendation for these agents as part of first-line therapy regimens in individuals with CKD and T2D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations